Preoperative Dynamic Hip Examination Under Fluoroscopic Guidance Enhances the Understanding of Femoroacetabular Impingement Pathology and Treatment Planning - Vitali Goriainov, B.M., F.R.C.S. (Orth); Laura Chapman, B.M; Fadi Hindi, M.B.Ch.B., M.R.C.S; Andrew J. Langdown, B.M., F.R.C.S. (Orth) (Elsevier, 2021)
Purpose: To review the relative accuracy of preoperative magnetic resonance imaging (MRI) and fluoroscopically guided examination-under-sedation (EUS) findings and to explore the validity of the anterior acetabular sector angle (AASA) as a radiologic MRI-based marker of anterior acetabular coverage in pincer-type impingement. Methods: A cohort of 150 consecutive patients undergoing primary hip arthroscopy for femoroacetabular impingement (FAI) in 2018 to 2019 was reviewed. The inclusion criteria were pure FAI unilateral symptomatic pathology and the availability of complete data sets (MRI, EUS, and intraoperative records). Preoperative MRI and EUS findings were compared with gold-standard intraoperative arthroscopic findings, specifically evaluating the alpha angle in the presence of cam lesions, AASA in the presence of pincer lesions, as well as soft-tissue lesions. An alpha angle greater than 50° and an AASA greater than 65° were deemed pathologic. Results: The patient cohort included 78 women and 72 men with an average age of 38 years (range, 18-53 years). Intraoperatively, pincer lesions were present in 20% of patients; cam lesions, 26%; and mixed impingement, 54%. MRI versus EUS correctly identified pincer lesions in 36% versus 89% of cases and identified cam lesions in 44% versus 77% of cases. MRI findings characterizing labral tears and articular cartilage pathology were accurate in 80% and 10% of cases, respectively. Although there was no difference in the AASA between pure pincer- and mixed-type impingements (62° and 63°, respectively; P = .62), there was a statistically significant difference in reported AASA values between pure cam-type impingement and impingement involving the presence of pincer lesions (57° and 63°, respectively; P = .03). Furthermore, 31% of patients with intraoperatively identified pincer lesions had an AASA of 60° to 65°. Conclusions: Fluoroscopic EUS is accurate in characterizing FAI pathology. In addition, MRI is useful to diagnose or rule out non-FAI pathology, ascertain labral pathology, and outline hip alignment. These methods of preoperative planning are complementary. Level of Evidence: Level IV, therapeutic case series.